Desirable Dense Neighbourhoods: An Environmental Psychological Approach for Understanding Community Resistance to Densification - Nematollahi, Shohreh (Curtin University, 2018)
This study investigates the underlying factors behind community resistance to increasing housing density in neighbourhoods. It aims to understand the dimensions of what a community would consider to be a ‘desired dense’ place or neighbourhood. This is conceived within the framework of a collaborative placemaking process built on a constructive dialogue between community and other stakeholders aimed at generating development proposals which might harmonise with the community’s perception of desirable living conditions.